Assessment of the relationship between periodontal disease and cardiovascular disorders: a questionnaire-based study - IONEL, ANCA (Clujul Med, 2016)
BACKGROUND AND AIMS: Periodontitis is an inflammatory disease, characterized by the loss of connective tissue and alveolar bone. There is an increasing evidence that periodontitis is associated with a number of chronic diseases. The aim of this study was to analyze the correlation between periodontitis and certain systemic diseases by identifying their risk factors in a population from North-West Romania. METHODS: A questionnaire-based study was conducted on participants ≥45 years of age in 4 dentistry or family medicine practices from the Cluj and Bihor counties, Romania, over a time frame spanning two months. The interviewer-administered questionnaire included 42 items assessing risk factors for periodontal and cardiovascular disease, current diagnostic and medical treatment of the participants, their diet and oral hygiene habits. RESULTS: Of 108 participants included in the study, 63 (58.3%) declared a previous diagnosis of periodontitis. A significant difference was observed between the participants with declared diagnosis of periodontitis (PD+) and participants without declared diagnosis of periodontitis (PD−) for fresh fruit consumption (p=0.01) and increased sport activity (p=0.009). A significant difference between groups was observed in the case of smoking duration (p=0.047), participants with >10 years of smoking were more likely to declare a diagnosis of periodontitis. Also, PD+ participants were more likely to have a family history of periodontal disease (p<0.001). Multivariate analyses suggested periodontitis as a predictive variable for atherosclerotic coronary artery disease with an OR of 4.85 (95% confidence interval 1.01–23.29, p=0.049). CONCLUSION: Our study found a statistically significant association between periodontal disease and a known family history of periodontal disorders and smoking duration. Daily intake of fresh fruit and increased sport activities were found to be protective factors against periodontal disease, while periodontitis was found as a risk factor for atherosclerotic cardiovascular disease.